2015
DOI: 10.1001/jamapediatrics.2014.3040
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Clinical Phenotypes of Preterm Birth Syndrome

Abstract: We identified 12 preterm birth phenotypes associated with different patterns of neonatal outcomes. In 22% of all preterm births, parturition started spontaneously and was not associated with any of the phenotypic conditions considered. We believe these results contribute to an improved understanding of this complex syndrome and provide an empirical basis to focus research on a more homogenous set of phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
104
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(113 citation statements)
references
References 36 publications
7
104
1
1
Order By: Relevance
“…2830;48 Our observation of risk across subtypes for preexisting hypertension, preexisting diabetes, and previous PTB are consistent with findings in Western Australia, Nova-Scotia, and in a recent World Health Organization (WHO) multi-country survey (Table S5). 2830 Our findings with respect to risk across groupings for preeclampsia and anemia are consistent with the WHO multi-country survey 32 but differ somewhat from those in Australia 30 where investigators found that anemia was only associated with PPROM and medically-indicated PTB and found that preeclampsia was only associated with preterm labor and medically-indicated PTB.…”
Section: Discussionsupporting
confidence: 87%
“…2830;48 Our observation of risk across subtypes for preexisting hypertension, preexisting diabetes, and previous PTB are consistent with findings in Western Australia, Nova-Scotia, and in a recent World Health Organization (WHO) multi-country survey (Table S5). 2830 Our findings with respect to risk across groupings for preeclampsia and anemia are consistent with the WHO multi-country survey 32 but differ somewhat from those in Australia 30 where investigators found that anemia was only associated with PPROM and medically-indicated PTB and found that preeclampsia was only associated with preterm labor and medically-indicated PTB.…”
Section: Discussionsupporting
confidence: 87%
“…First, as preterm birth is often described as a syndrome [24], this study will allow for nested studies examining maternal, fetal, and placental risk factors that contribute to preterm birth. As such, preterm birth phenotyping studies using the framework described by Barros et al (2012) will be nested at some of our sites [25]. Second, as GA assessment will prove to be a challenge in many of our sites, this poses a unique opportunity to test other measures to more accurately estimate GA.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous preterm birth (sPTB) was formerly divided into two general categories, namely cervical dysfunction ( cervical insufficiency or cervical incompetence ) or preterm labor (typically thought to be the result of intrauterine infection or bleeding). A more current understanding is that sPTB from all causes can be seen as part of an extremely complex continuum involving multiple phenotypes (Barros et al, 2015; Solomon and Iams, 2014). The etiology of sPTB is multifactorial, involving diverse precipitating factors such as infection and inflammation, bleeding, poor nutrition, demographics, stress, ethnicity and race, genetic predispositions and many others, all presumably with individual, and overlapping, molecular mechanisms (Gravett et al, 2010).…”
Section: The Clinical Problem Of Preterm Birthmentioning
confidence: 99%
“…The etiology of sPTB is multifactorial, involving diverse precipitating factors such as infection and inflammation, bleeding, poor nutrition, demographics, stress, ethnicity and race, genetic predispositions and many others, all presumably with individual, and overlapping, molecular mechanisms (Gravett et al, 2010). A recent attempt to categorize phenotypes of preterm birth showed that approximately 25% of these births are neither medically indicated nor associated with any known phenotype (Barros et al, 2015). …”
Section: The Clinical Problem Of Preterm Birthmentioning
confidence: 99%